Influence of raw-material quality and process parameters in the production of insulation cork agglomerates - Pereira, H.; Baptista, C. (European Journal of Wood and Wood Products, 1993)
{Insulation cork agglomerates are produced with different low-cost raw-materials unsuitable for other products: virgin corks (from prunmgs, thinnings anti dead trees), reproduction corks (refuse and underaged) and industrial byproducts (corkback strips). These materials were analysed in relation to chemical composition, struc- ture and trituration behaviour. The industrial byproducts diffcr significantly from the other materials due to the presence of an important amount of the unsubcriscd lignocellulosic phlocm (the back of the corkboards) in a way that is detrimental to the agglomeration process. The influence of raw-material, granulometry and process parameters (time, temperature and pressure} were studied using an experimental autoclave. Temperature is the deter- mining factor for agglomeration. Insufficient adhesion is obtained under 230 ~C and adequate agglomeration is attained only with temperatures in the range 230 300 "C. corresponding to inass losses of 10 25%.
Keywords: chemical composition; CORK AGGLOMERATES; Raw materials; structure; trituration behaviour (Voyant)